Hydride-vapor-phase epitaxial growth of highly pure GaN layers with smooth as-grown surfaces on freestanding GaN substrates. (21st July 2017) - Fujikura, Hajime; Konno, Taichiro; Yoshida, Takehiro; Horikiri, Fumimasa
Abstract: Thick (20–30 µm) layers of highly pure GaN with device-quality smooth as-grown surfaces were prepared on freestanding GaN substrates by using our advanced hydride-vapor-phase epitaxy (HVPE) system. Removal of quartz parts from the HVPE system markedly reduced concentrations of residual impurities to below the limits of detection by secondary-ion mass spectrometry. Appropriate gas-flow management in the HVPE system realized device-quality, smooth, as-grown surfaces with an excellent uniformity of thickness. The undoped GaN layer showed insulating properties. By Si doping, the electron concentration could be controlled over a wide range, down to 2 × 10 14 cm −3, with a maximum mobility of 1150 cm 2 ·V −1 ·s −1 . The concentration of residual deep levels in lightly Si-doped layers was in the 10 14 cm −3 range or less throughout the entire 2-in. wafer surface. These achievements clearly demonstrate the potential of HVPE as a tool for epitaxial growth of power-device structures.